The Role of Virtual Try-On Technology in Online Purchasing Decision - TUNCALI YAMAN, TUTKU (My University, 2022)
oday, with the intensive use of internet technologies, the concept of e-commerce became a focused channel to understand the customer behavior and purchasing processes for different product categories. Several methods are used to enable users to conclude their surf with the purchase and up-to-date technologies are contributed to positively nudging their purchasing tendencies. In this study, the impact of one of these technologies, virtual try-on (VTO), in terms of the customer experience was investigated. According to the results, the desire to use this technology again has been determined and it has also been seen that VTO technology had increased users’ purchase intention. Plus, two different user groups with different characteristics were identified according to their perceptions towards VTO technology. It is recommended that firms offering this technology seek to differentiate ways in their promotion and communication with designated groups.

Günümüzde internet teknolojilerinin yoğun kullanımı ile birlikte e-ticaret kavramı, farklı ürün kategorileri için müşteri davranışlarını ve satın alma süreçlerini anlamaya odaklı bir kanal haline gelmiştir. Kullanıcıların çevrimiçi satış sitesi ziyaretlerini satın alma ile tamamlamaları için çeşitli yöntemler kullanılmakta ve güncel teknolojilerle, satın alma eğilimlerinin olumlu yönde etkilenmesine katkıda bulunulmaktadır. Bu çalışmada, bu teknolojilerden biri olan sanal prova teknolojisinin müşteri deneyimi açısından etkisi araştırılmıştır. Elde edilen sonuçlara göre bu teknolojiyi tekrar kullanma isteği belirlenmiş ve ayrıca sanal prova teknolojisinin kullanıcıların satın alma niyetini arttırdığı görülmüştür. Ayrıca sanal prova teknolojisine yönelik algılarına göre, farklı özelliklere sahip iki farklı kullanıcı grubu belirlenmiştir. Bu teknolojiyi sunan firmaların, belirlenen gruplarla tanıtım ve iletişimlerinde farklılaştırma yollarını araması önerilmektedir.
Keywords: Sanal Prova; Dijital etkileşim; E-ticaret; Segmentasyon; Virtual Try-On; Digital interaction; E-commerce; Segmentation